Evaluating the diagnostic sensitivity of computed diffusion‐weighted MR imaging in the detection of breast cancer. Issue 1 (13th January 2016) - O'Flynn, Elizabeth A.M.; Blackledge, Matthew; Collins, David; Downey, Katherine; Doran, Simon; Patel, Hardik; Dumonteil, Sam; Mok, Wing; Leach, Martin O; Koh, Dow‐Mu
Abstract : Purpose: To evaluate the diagnostic sensitivity of computed diffusion‐weighted (DW)‐MR imaging for the detection of breast cancer. Materials and Methods: Local research ethics approval was obtained. A total of 61 women (median 48 years) underwent dynamic contrast enhanced (DCE)‐ and DW‐MR between January 2011 and March 2012, including 27 with breast cancer on core biopsy and 34 normal cases. Standard ADC maps using all four b values (0, 350, 700, 1150) were used to generate computed DW‐MR images at b = 1500 s/mm 2 and b = 2000 s/mm 2 . Four image sets were read sequentially by two readers: acquired b = 1150 s/mm 2, computed b = 1500 s/mm 2 and b = 2000 s/mm 2, and DCE‐MR at an early time point. Cancer detection was rated using a five‐point scale; image quality and background suppression were rated using a four‐point scale. The diagnostic sensitivity for breast cancer detection was compared using the McNemar test and inter‐reader agreement with a Kappa value. Results: Computed DW‐MR resulted in higher overall diagnostic sensitivity with b = 2000 s/mm 2 having a mean diagnostic sensitivity of 76% (range 49.8‐93.7%) and b = 1500 s/mm 2 having a mean diagnostic sensitivity of 70.3% (range 32‐97.7%) compared with 44.4% (range 25.5‐64.7%) for acquired b = 1150 s/mm 2 (both p = 0.0001). Computed DW‐MR images produced better image quality and background suppression (mean scores for both readers: 2.55 and 2.9 for b 1500 s/mm 2 ; 2.55 and 3.15 for b 2000 s/mm 2, respectively) than the acquired b value 1150 s/mm 2 images (mean scores for both readers: 2.4 and 2.45, respectively). Conclusion: Computed DW‐MR imaging has the potential to improve the diagnostic sensitivity of breast cancer detection compared to acquired DW‐MR. J. Magn. Reson. Imaging 2016;44:130–137.